Design of a Digital Map to Support Coffee Shop Tourism Guided by the Ambeu Preanger Community in Pangalengan District - Agung, Lingga; Putra, Wibisono Tegar Guna; Maharani, Adinda; Ramadhan, Iqbal Raihan (Universitas Pendidikan Indonesia, 2022)
Pangalengan is one of the tourist destinations in West Java that is currently popular and has resulted in an increase in the number of tourists. This density occurs especially in tourist attractions that have quite big names. One of the advantages of Pangalengan is coffee, which is known as the best coffee commodity in West Java. However, the existence of a coffee shop in the Pangalengan area has not been able to encourage the growing interest of tourists to come to the coffee shop. One of the problems faced is the absence of mapping which is a source of information on the existence of coffee shops in the Pangalengan area. This research used the 4D RD method consisting of 4 main stages namely Define, Design, Develop, and Disseminate which were carried out at the Ambeu Preanger Coffee Farming Community. The results of the study show that one of the causes of the non-publication of coffee shops in the Pangalengan area is caused by the information media which does not expose coffee shops as a tourism commodity. The existence of a digital map is considered to be able to support the tour of the Ambeu Preanger Community Assisted Coffee Shop in Pangalengan District so it is hoped that with a digital map that specializes in the shops above it will become better known and will certainly generate good profits for the continuity of its business